Active circuit design and simulation using LTspice - Chia, Yuan Tzeng (Nanyang Technological University, 2021)
In this report, active rectifier system is designed using low power high speed operational amplifiers. Active rectifier system is designed to convert AC signals into DC signals for general purpose. The performance of these circuit systems is analyzed using LTspice software. To analyse the behaviour of circuits, simulated circuits are constructed using circuit theory analysis and power electronics knowledge. Experimental results obtained are further discussed to provide future recommendation for the use of this active rectifier system.